Estimation of Remnant Dentin Thickness under Proximal Caries Using Digital Bitewing Radiography: An In-Vitro Study - Masoomeh Afsa; Asma Zangizade; Ghader Zargaran (Mashhad University of Medical Sciences, 2016)
Objectives: In restorative dentistry, it is essential to estimate the amount of remnant tooth structure after caries removal to make the best treatment plan. The present study was aimed to determine whether there is a correlation between the real thickness of remnant dentin under carious lesion and the radiographical measurement from photostimulable phosphor plates (PSPs). Methods: a whole number of 68 unrestored permanent human molar and premolar teeth with 82 proximal carious surfaces were mounted in an artificial arch. Digital bitewing radiographs with PSPs were taken, carious lesions were removed and radiographic imaging was repeated. Teeth were sectioned mesiodistally in two parts and thickness of remnant tooth structure to pulp was measured. Measurements of remnant dentin under caries from radiographic images and teeth structures were compared. Result: The mean measurements of remnant dentin on primary radiographs were statistically different from the measurements on teeth structures. The mean thickness of remnant dentin on tooth structure was around 30% less than what measured on radiographic image. Conclusion: The real thickness of remnant dentin under caries is about 70% of its thickness measured on digital bitewing radiographs prepared by PSPs as image receptor.